Hepatitis B seroprevalence in hematological oncology patients - Turken, Melda; Köse, Şükran; Özkan Acar, Ayşe; Ceylan, Cengiz; Albayrak, Hazal; Arkalı, Eren (The European Research Journal, 2020)
Objectives: Hepatitis B virus (HBV) infection is still a serious public health problem today. Many factors such as frequent blood transfusion, hemodialysis, sexual contact, sterilization in surgical procedures, etc. are involved in the transmission of hepatitis B virus. In our study, HBV seroprevalence was evaluated retrospectively in order to provide vaccination of anti-HBs negative patients and to determine HBV prophylaxis in patients with hematological malignancy. Methods: A total of 499 patients were included in the study. HBsAg, anti-HBs, anti-HBc IgG, anti-HDV, HBV DNA values were measured by ELISA (enzyme-linked immunosorbent assay, Liason, Diasorin, Italy) with Real-Time PCR (Cobas-Tagman, Roche Switzerland) and recorded. The obtained datas were evaluated by SPSS for Windows 15.00 statistical program. A value of p <0.05 was accepted as a statistical significance value. Results: HBsAg positivity was found to be 3.4% (n = 17) in all patients. Appropriate treatment regimens were started to patients with HBsAg (+). There were 166 (33.3%) patients with anti-HBs (+). One hundred nineteen (23.8%) patients had anti-HBc IgG (+), 40 (33.6%) of them were started a prophylactic treatment regimen. Anti-HBs positivity were reported after vaccination in 48 (16.8%) patients. Occult hepatitis have not been detected in patients with anti-HBc IgG positivity. Conclusions: As a result of this study, anti-HBs negative patients with hematological malignancies were vaccinated. Patients and physicians should be informed about vaccination and hepatitis serology controls of hematological malignancy and other immunosuppressed patients. Sensitivity in this context should be increased in terms of prophylactic treatments.